Image analysis system of rice seed based on Matlab platform - CHENG Fang; YING Yi-bin (浙江大学学报. 农业与生命科学版)
Image analysis of rice seeds should be addressed before an automatic inspecting system can be developed. Such analysis based on Matlab platform was attempted. The main function of the image analysis system include pre-processing single static rice seed image, extracting 23 features of dimension, shape and color, recognizing cultivars of Jinyou402, Shanyou10, Zhongyou207, Jiayou99 and Ilyou3207, detecting defects of germination, disease and unclosed glumes.